Stress-Strain Behaviour Of Conductive Polymer - Yusri, Akmal (Universiti Sains Malaysia, 2022)
Due to an increasing demand on the use of the conductive ink in the market, many researchers have produced plenty of conductive ink and pairs it with different types of substrates. The goals of this study were to evaluate the performance of 2 different conductive ink which is Ag-PDMS ink and Ag liquid ink with the use of Polyurethane as the substrate. To get the materials properties for both the conductive ink, Nano indentation test was done to get the Elastic modulus of the inks. While for the polyurethane substrate a uniaxial tensile test was done to get the stress strain curve to build the Neo-Hookean model for the simulation. The evaluation was done by using ANSYS software get the stress value of the conductive ink. Three printing shape was used to compare which printing shape was better for both conductive ink for the Ag-PDMS ink the displacement was set to 30 mm while for the Ag liquid ink it was set to 10 mm. From the result that we get it shows that for the Ag-PDMS ink we can see that the zigzag shape is the best with lower maximum stress followed by the straight and horseshoe. While for the Ag liquid ink we can see that the zigzag is the best with lower maximum stress followed by the horseshoe and straight shape.